Pengembangan Media Motion Book IPAS Berbasis Budaya Lokal Jember untuk Menanamkan Cinta Tanah Air Pada Murid SD - Dara Yuniar Dwi Agustin (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to develop a Motion Book as an interactive learning media based on Jember’s local culture to foster elementary school students’ sense of patriotism. The study employed the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The analysis phase included problem identification, needs assessment, and analysis of learners’ characteristics. The Motion Book was designed by integrating IPAS content with elements of Jember’s local culture to create meaningful and contextual learning experiences. The developed product was validated by experts to determine its feasibility, followed by practicality and effectiveness testing. The results indicate that the Motion Book is valid, practical, and effective in enhancing students’ understanding of the learning material and in fostering their sense of patriotism. Therefore, the Motion Book can serve as an innovative learning medium to support elementary education.
Finalisasi 23 Juli 2026 Rudi H
Keywords: IPAS; Cinta Tanah Air; Media Motion Book; Budaya Lokal Jember